Guillain-Barré syndrome - Willison, Hugh J; Jacobs, Bart C; van Doorn, Pieter A (The Lancet (British edition), 2016)
Guillain-Barré syndrome is the most common and most severe acute paralytic neuropathy, with about 100 000 people developing the disorder every year worldwide. Under the umbrella term of Guillain-Barré syndrome are several recognisable variants with distinct clinical and pathological features. The severe, generalised manifestation of Guillain-Barré syndrome with respiratory failure affects 20–30% of cases. Treatment with intravenous immunoglobulin or plasma exchange is the optimal management approach, alongside supportive care. Understanding of the infectious triggers and immunological and pathological mechanisms has advanced substantially in the past 10 years, and is guiding clinical trials investigating new treatments. Investigators of large, worldwide, collaborative studies of the spectrum of Guillain-Barré syndrome are accruing data for clinical and biological databases to inform the development of outcome predictors and disease biomarkers. Such studies are transforming the clinical and scientific landscape of acute autoimmune neuropathies.